Efficacy of one-hour negative pressure wound therapy and magnetic field energy in wound healing - Özer, Aysel Yıldız; Keskin, İlknur; Keleştemur, Taha; Aytürk, Nilüfer; Ersavaş, Cenk; Günal, Mehmet Yalçın (MA Healthcare Ltd, 2024)
Objective: Wound healing is an important aspect of health but needs further research to identify the effects and interactions of different treatment approaches on healing. The aims of this study were to investigate the effectiveness of one-hour negative pressure wound therapy (NPWT) and compare histological differences between one-hour NPWT and magnetic field energy (MFE) in rats on early-stage wound healing, wound size and angiogenesis. Method: Standardised wounds were created on Wistar rats that were allocated and divided into NPWT, MFE and control groups. Both treatments were applied for 1 hour/day for 10 days. Wound size, histological changes and wound area blood flow were assessed. Results: The wound size of all groups was similar on days 0, 2 and 10. The MFE group s wound size was smaller than the NPWT group on days 4, 6 and 8 (p.
Keywords: Wound Healing; Magnetic Field Energy; Negative Pressure